Survey of Health Services Utilization and Expenditures, 1970 ([Verlag nicht ermittelbar], 1984)
This national survey was conducted to compare health services utilization and expenditures in 1970 with results of similar studies done in 1953, 1958, and 1964. In the survey, respondents from 3,763 families plus additional older individuals -- a total of 11,619 persons -- were interviewed in 1971. One or more persons in each family provided information regarding use of health services, the cost of such services, and how these costs were met for the calendar year 1970. Information was also collected on perceptions of illness and health, attitudes and opinions about medical care in the United States, and health beliefs. An attempt was made to verify all hospital admissions, physician visits, and insurance reports and claims. These verifications had two purposes: first, to determine if the reported care was, in fact, provided during the survey year, and second, to elicit more precise information than the families were likely to give on diagnoses, costs, kinds of treatment, and sources of payment for services. Verification data were obtained for over 90 percent of the hospital admissions and for two-thirds of the physician visits. Demographic data were also collected, including age, sex, race, education, occupation, income, and place of residence.